The Role of Parent Communication in Accompanying Children during the Covid-19 Pandemic (Analysis Study of Family in Gampong Matang Bayu, Baktiya Barat District, Aceh Utara Regency) - Khairun Asyura; Fauzan Fauzan; Nurasmi Nurasmi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Communication is very important in all areas of life, especially during the Covid-19 pandemic, especially in a family, parental communication is very important for children, where parents are novice teachers for children. This study uses a qualitative method with a descriptive analysis approach. In the sense of seeing the extent of the role of parental communication in accompanying children during the COVID-19 pandemic and what obstacles and support were carried out by parents in assisting children during the COVID-19 pandemic in Gampong Matang Bayu, Baktiya Barat District, North Aceh Regency by way of interviews, observations and documentation then the data that has been collected is analyzed. The results of the study can be seen that the role of parental communication in accompanying children during the COVID-19 pandemic is very effective, for example giving motivation to children, inviting children to study together, building intimacy in communicating with children, keeping the house clean and reminding children to always wash their hands. and feet every time they enter the house. The supporting factors are the existence of a gampong study center which is active as usual so that parents feel a little lighter in communicating, there is direction and guidance from school teachers even though it is done online. While the inhibiting factor is that parents do not understand how to operate cellphones so that they do not optimally control children when using cellphones, parents have difficulty understanding learning material from school, parents do not have enough time, even it is difficult in terms of economy in filling pulses, so that there is a lack of patience and also find it difficult to cultivate children's interest in learning.